Towards efficient membrane filtration for microalgae harvesting : a review - Nur Farahah Mohd Khairuddin; Ani Idris; Irfan, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Microalgae contain pigments such as chlorophyll and ß-carotene that are found to be useful as ingredients in human foods. Downstream processing is the key step to obtain the pigments but before that, harvesting process is required. The purpose of harvesting is to separate the microalgae cells from its culture media. There are many harvesting methods including membrane filtration. Besides simple in operation, membrane filtration technology involves no chemicals, no phase changes and offers complete solid retention. However, high flux requirement and reducing operating and maintenance cost of membrane filtration are challenges for microalgae harvesting. Another issue with membrane filtration is membrane fouling. One of the common approaches used currently in anti-fouling harvesting is by modifying the configuration of the filtration system itself by adding auxiliaries such as air scouring and vibration into the filtration systems. Thus, this review covers recent microalgae species that have been harvested by membrane filtration and their efficiency. Chlorella vulgaris, Nannochloropsis oculata and Scenedesmus sp. are among the species that have been harvested using membranes. Techniques that can be applied for tailoring membrane filtration to be a universal harvesting method for all microalgae species are also highlighted. Having this in mind, factors such as membrane formulation and types of membrane making process which play significant roles in determining the efficiency of harvesting were discussed.